2015
DOI: 10.1080/13645579.2015.1062624
|View full text |Cite
|
Sign up to set email alerts
|

Embedding quantitative skills into the social science curriculum: case studies from Manchester

Abstract: Those aiming to respond to the recognised shortage in quantitative skills within the UK social sciences have increasingly focused on the content of undergraduate degree programmes. Problems occur when 'quantitative methods (QM)' are generally confined to a dedicated module, detached from substantive topics. This model makes it hard for students to understand or engage with the contribution of quantitative research to their discipline and can perpetuate negative perceptions of quantitative training. We suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
(22 reference statements)
1
25
0
Order By: Relevance
“…These studies suggest that a curriculum‐wide approach to attitude improvement would be more effective than a course‐by‐course approach. Many scholars have thus lobbied for a more “integrative approach” to teaching quantitative methods (Adeney & Carey, ; Buckley et al, ; Henshaw & Meinke, ; Howery & Rodriguez, ; Slootmaeckers et al, ). For instance, Henshaw and Meinke () took the idea of the “integrative approach” into practice and investigated how quantitative analysis could be useful in nonmethods courses and improve students' critical reasoning skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that a curriculum‐wide approach to attitude improvement would be more effective than a course‐by‐course approach. Many scholars have thus lobbied for a more “integrative approach” to teaching quantitative methods (Adeney & Carey, ; Buckley et al, ; Henshaw & Meinke, ; Howery & Rodriguez, ; Slootmaeckers et al, ). For instance, Henshaw and Meinke () took the idea of the “integrative approach” into practice and investigated how quantitative analysis could be useful in nonmethods courses and improve students' critical reasoning skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kounine, Marks, and Truss () estimate a loss of £9 billion incurred by the British economy due to the decline in quantitative skills among younger generations and the lack of a comprehensive approach to teaching quantitative methods at the curriculum level. The academic community expresses similar fears (Adeney & Carey, ; Buckley, Brown, Thomson, Olsen, & Carter, ; Noyes & Adkins, ).…”
Section: Introductionmentioning
confidence: 95%
“…In line with recent findings on successful practices in methods teaching, we work on the principle of embedding grounded learning activities within the narrative of research design and implementation (Buckley, Brown, Thomson, Olsen, & Carter, 2015). Effective learning of data skills within social science research methods teaching was found by Kilburn, Nind, and Wiles (2014a) to be achieved through three means: active learning by making processes visible; directly experiencing methods; and critical reflection on practice.…”
Section: Introductionmentioning
confidence: 95%
“…However, these data are usually expedient and connections with theory or literature may be tenuous. In research methods education, examples of case studies with elements of action research demonstrate efforts to share practice (see Buckley et al 2015;Scott Jones and Goldring 2015). However, teacher-researchers do not necessarily equate this with doing pedagogic research, as pedagogic research is often outside of methods teachers' own disciplinary domains.…”
Section: Researching Pedagogy Within Research Methods Educationmentioning
confidence: 99%